Fostering a Diverse Pool of Global Health Academic Leaders Through Mentorship and Career Path Planning. (22nd November 2019) - Newberry, Jennifer A.; Patel, Shama; Kayden, Stephanie; O'Laughlin, Kelli N.; Cioè‐Peña, Eric; Strehlow, Matthew C.
Abstract: Established in 2011, the Global Emergency Medicine Academy (GEMA) aims "to improve the global delivery of emergency care through research, education, and mentorship." Global health remains early in its development as an academic track in emergency medicine, and there are only a small number of global emergency medicine academic faculty in most institutions. Consequently, GEMA focused its efforts at the Society for Academic Emergency Medicine (SAEM) Annual Meeting in 2019 on developing a diverse pool of global health academics and leaders in emergency medicine. Current and previous members of the GEMA Executive Committee convened to appraise and describe how current GEMA efforts situate within existing knowledge in the arenas of professional development and mentorship. The 2019 SAEM Annual Meeting unveiled the Global Emergency Medicine Roadmap, a joint venture between GEMA and the residents and medical students (RAMS) group. The roadmap guides medical students, residents, and fellows in the exploration of global emergency medicine and career development. GEMA's mentorship roundtable complemented this effort by providing a version of speed mentoring across several critical areas: work–life balance, identifying near‐peer and long‐distance mentoring opportunities, negotiating with your Chair, finding funding, networking, and teaching abroad. Finally, the GEMA‐sponsored panel "Empowering Women through Emergency Care Development in LMICs" underscored the potential for empowering women through global emergency medicine development, including policy advocacy, inclusive research approaches, and mentorship and sponsorship. In summary, GEMA is committed to developing a diverse group of future global health leaders to guide the expansion of emergency medicine worldwide. Our work indicates critical future directions in global emergency medicine education and training including building innovative mentoring networks across institutions and countries. Further, we will continue to focus on growing faculty diversity, empowering underrepresented populations through emergency care development, and supporting rising global emergency medicine faculty in their pursuit of advancement and promotion.